The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1063/1.4721627
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical study of the nuclear spin-molecular rotation coupling for relativistic electrons and non-relativistic nuclei

Abstract: A theoretical study of the relation between the relativistic formulation of the nuclear magnetic shielding and spin-rotation tensors is presented. To this end a theoretical expression of the relativistic spin-rotation tensor is formulated, considering a molecular Hamiltonian of relativistic electrons and non-relativistic nuclei. Molecular rotation effects are introduced considering the terms of the Born-Oppenheimer decomposition, which couple the electrons and nuclei dynamics. The loss of the simple relation l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
125
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(131 citation statements)
references
References 31 publications
(46 reference statements)
3
125
0
Order By: Relevance
“…In Ref. 6, we developed a theoretical formalism based on first order corrections to the BO approximation. 8 The zeroth order molecular wave function is expressed as the product…”
Section: A Relativistic 4-component Expression Of the Spin-rotation mentioning
confidence: 99%
See 3 more Smart Citations
“…In Ref. 6, we developed a theoretical formalism based on first order corrections to the BO approximation. 8 The zeroth order molecular wave function is expressed as the product…”
Section: A Relativistic 4-component Expression Of the Spin-rotation mentioning
confidence: 99%
“…Taking the equilibrium configuration as starting point and neglecting vibrational effects, the Hamiltonian for the nuclei is the one corresponding to a purely rotating system described by the rigid rotor Hamiltonian, 6, 11…”
Section: A Relativistic 4-component Expression Of the Spin-rotation mentioning
confidence: 99%
See 2 more Smart Citations
“…In this work, the authors also addressed the correspondence between the paramagnetic shielding and the nuclear-spinmolecular-rotation coupling constant [180]. The latter point was more thoroughly investigated in a follow-up study [181]. Within the applied approximations, it was found that the analogy between the two properties does not extend into the relativistic regime.…”
Section: Dks X2c-ksmentioning
confidence: 99%